International mixed methods study protocol to develop a patient-reported outcome measure for all types of chronic wounds (the WOUND-Q). Issue 3 (25th March 2020) - Klassen, Anne; van Haren, Emiel LWG; Cross, Karen; Fan, Kenneth L; Gibbons, Chris; Hoogbergen, Maarten M; Longmire, Natasha M; Poulsen, Lotte; Sorensen, Jens Ahm; Squitieri, Lee; Tsangaris, Elena; van Alphen, Tert C; et al.
Abstract : Introduction: Most patient-reported outcome measures (PROM) for chronic wounds are specific to a single wound type (eg, pressure ulcer) or part of the body. A barrier to outcome assessment in wound care and research is the lack of a rigorously designed PROM that can be used across wound types and locations. This mixed method study describes the protocol for an international collaboration to develop and validate a new PROM called the WOUND-Q for adults with chronic wounds. Methods and analysis: In phase I, the qualitative approach of interpretive description is used to elicit concepts important to people with wounds regarding outcome. Participants from Canada, Denmark, the Netherlands, and the USA are aged 18 years and older and have a wound that has lasted 3 months or longer. Interviews are digitally recorded, transcribed and coded. A conceptual framework and preliminary item pool are developed from the qualitative dataset. Draft scales are formed to cover important themes in the conceptual framework. These scales are refined using feedback from people with chronic wounds and wound care experts. After refinement, the scales are translated into Danish and Dutch, following rigorous methods, to prepare for an international field-test study. In phase II, data are collected in Canada, Denmark, the Netherlands, and the USA. An international sample of people with a large variety of chronic wounds complete the WOUND-Q. Rasch Measurement Theory analysis is used to identify the best subset of items to retain for each scale and to examine reliability and validity. Ethics and dissemination: This study is coordinated at Brigham and Women's Hospital (Boston, USA). Ethics board approval was received at each participating site for both study phases. Findings will be published in peer-reviewed journals and presented at national and international conferences and meetings.